Profile of Sigmoid Diverticulitis Patients at RSUD DR. Soetomo Surabaya from 2019 to 2024 - Immanuel Van Donn Batubara (Riviera Publishing, 2025)
This study investigates the profile of patients with sigmoid diverticulitis treated at RSUD Dr. Soetomo Surabaya from June 2019 to June 2024. Diverticulitis is a prevalent non-cancerous pathology of the colon, predominantly affecting elderly individuals, and its incidence is increasing. The study aims to describe clinical characteristics, outcomes, Length of Stay (LOS), and complications associated with sigmoid diverticulitis. An observational analytic design was employed, analyzing case report data gathered during the specified period. Results indicate a higher prevalence in males, with significant age variation among patients. The study found a high incidence of complications, with a notable length of hospital stay correlated to the severity classified by the Hinchey grading system. These findings underscore the need for effective management strategies in treating sigmoid diverticulitis and lay the groundwork for future research in this area.